De novo protein crystal structure determination from X-ray free-electron laser data: letter - Barends, Thomas R. M.; Foucar, Lutz Michael; Botha, Sabine; Doak, R. Bruce; Shoeman, Robert L.; Nass, Karol; Koglin, Jason E.; Williams, Garth J.; Boutet, Sébastien; Messerschmidt, Marc; Schlichting, Ilme (Nature, 2014)
Femtosecond crystallography with an X-ray free-electron laser is used to analyse micrometre-sized protein crystals, generating a high-resolution structure of the protein without previous knowledge of what it looks like.
Published: 24 November 2013
Gesehen am 28.09.2021